Compactação do solo causada pelos tratores florestais harvester e forwarder na colheita de Pinus taeda L. - Szymczak, Denise Andréia (2013)
Soil compaction has been becoming one of the main impacts caused by the activities of mechanized harvesting. The weight and movement of machines at the time of cutting and loading of timber combined with the not appropriate moisture condition of the soil are the main causes of soil structural degradation, observed mainly by changes in soil physical properties. Thus, this study aimed to identify soil compaction caused due to forest harvesting stages of Pinus taeda L. performed on three different soil moistures. A study in the city of Quedas do Iguaçu in southwestern Paraná was carried out in pine stands of Araupel S/A company. The research was assessed as completely randomized in and sub-subdivide plots with five replications. The eighteen treatments consisted of the interaction of three factors, namely: moisture (rainy day harvesting and 3 and 7 days after rain); harvesting operations (machine traffic (MT); no machine traffic (NMT) and timer landing (TL)); and time of collection (before and after harvest), being major plot, subdivided plots, and sub-subdivided plots in time, respectively. Soil under a native forest adjacent to the experiment was evaluated to infer on the changes caused to the soil regarding its cultivation and management. Results indicated that the difference in soil moisture represented by the different days of harvest after a rain did not influence differently the soil compaction. On the other hand, harvesting operations (MT, NMT and TL) impacted soil to a depth of 10 cm causing compaction on the traffic lines of the machines, while the eventual falling trees at the time of cutting and timber landing did not cause changes in density, macroporosity and resistance to penetration. The residual biomass from forest harvesting was essential to minimize soil compaction caused by machinery traffic that was close to the maximum. Comparison of physical parameters of soil under native forest and pine stand showed that planting and management of soils covered by natural forests alter the physical properties of the surface until 30 cm of depth.